Main trends of researches in history of informatics - Voverienė, Ona (Knygotyra, 2024)
Analysis of the abstract journal Informatics showed that the heading "History of Informatics and Scientific Information Activities" was established in 1966 and, except for its interruption in 1970-1976, has continued to this day. Under this heading, 96 abstracts of publications devoted to the history of informatics and librarianship have been published. The investigation of subjects revealed that the main trends in the history of informatics research are as follows: problems of its origin; history of the organization of scientific information activities; genesis of its main terms and categories; and analysis and appreciation of the contributions of some scientists to informatics.The article discusses the main conceptions about the origin of informatics, provides a review of publications related to the history of scientific information activities in our country, and surveys appraisals of scientists and their contributions to the development of informatics.
Keywords: -